2018
DOI: 10.1245/s10434-018-6405-x
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Impact of Body Mass Index on the Tumor Microenvironment in Colon Cancer: Results of a Prospective Trial

Abstract: Tumor mismatch repair status and obesity are correlated in patients with colon cancer. Increased intratumoral T cells in nonobese patients suggests an unexplored link between tumor mismatch repair and immunoprofile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A comprehensive study of TIL/Tc infiltration abundance and geography, neoantigen specificity, clonal expansion and phenotypic subsets in the tumour niche is paramount to advancing our understanding of the mechanisms that drive tumour immune escape mechanisms. Additionally, due to the lack of detailed information about patient body mass index and systemic treatment in the cohorts we investigated, it was impossible to investigate any relationship between obesity and tumour infiltration [ 64 ] or determine the impact of different therapies on survival [ 38 ]. Therefore, we endorse validation in prospective series, particularly in the ICIs scenario, also using targeted TCR sequencing tools that, by increasing the detection power for TCR sequences [ 17 ], can facilitate the standardisation of optimal cut-offs and the qualification of TCR -based biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive study of TIL/Tc infiltration abundance and geography, neoantigen specificity, clonal expansion and phenotypic subsets in the tumour niche is paramount to advancing our understanding of the mechanisms that drive tumour immune escape mechanisms. Additionally, due to the lack of detailed information about patient body mass index and systemic treatment in the cohorts we investigated, it was impossible to investigate any relationship between obesity and tumour infiltration [ 64 ] or determine the impact of different therapies on survival [ 38 ]. Therefore, we endorse validation in prospective series, particularly in the ICIs scenario, also using targeted TCR sequencing tools that, by increasing the detection power for TCR sequences [ 17 ], can facilitate the standardisation of optimal cut-offs and the qualification of TCR -based biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a small subgroup of patients with CRC featuring mismatch repair deficiency (dMMR) were demonstrated to exhibit better outcomes than those with mismatch repair-proficient tumors (pMMR) in certain stage cases, such as stage II ( 60 , 61 ), and they also had a significantly good response when receiving immunotherapies in metastatic cases when compared to pMMR cases ( 62 ). Notably, a lower BMI was found to be more common in patients with dMMR than in those with pMMR ( 63 ); additionally, CEA levels were significantly higher in the pMMR subtype (but only in stage III patients) ( 64 ). These results suggested that for patients in certain stages, the CBR would be higher than for those in other stages.…”
Section: Discussionmentioning
confidence: 99%